Legal Analysis of Metaverse Banking from the Perspective of Islamic Economics - Redi Hadianto; Aulia Aniatun Nisa (Universitas Ahmad Dahlan, 2025)
Introduction to The Problem: The emergence of the metaverse banking concept is a consequence of advances in virtual world technology. However, its implementation raises various legal issues that still lack clarity, particularly in the context of Islamic economics. Therefore, in-depth research is needed to ensure that future digital banking services align with the principles of Sharia. This study includes important issues such as ownership of digital assets, clarity of the legal status of virtual transactions, and the extent to which these activities conform to Islamic teachings. Purpose/Objective Study: In order to implement metaverse banking in Indonesia, this research aims to develop a legal framework that complies with sharia provisions, identify potential violations of sharia principles in virtual banking operations, and analyze the legal aspects of metaverse banking from the perspective of sharia economics. Design/Methodology/Approach: State the article’s design/methodology/approach used in the paper. This research uses a qualitative methodology that combines normative analysis and library research techniques. The Quran, Hadith, fatwas from DSN-MUI, regulations, and scientific works related to sharia economics and metaverse banking are studied to gather data. A comparative method between metaverse banking practices and sharia principles is used to conduct the analysis. Findings: The findings of this study indicate that if metaverse banking meets the requirements of transparency, avoids usury and uncertainty, and guarantees halal underlying assets, then it can comply with the principles of Islamic economics. However, the unique nature of virtual transactions and the need for strict oversight of security features and consumer protection in the metaverse environment require additional regulatory modifications.